Does kinesiology taping of the ankles affect proprioceptive control in professional football (soccer) players?. (May 2017) - Bailey, Daniel; Firth, Paul
Abstract: Objective: To determine whether the bilateral application of kinesiology tape (KT) to professional footballers' ankles can improve their lower limb proprioception. Design: A single blind randomised crossover study. Participants were randomly assigned to complete a proprioception test in either a taped or not taped condition first. Following a wash out period, participants were then re-tested in the alternate condition. Setting: A UK Championship League Football Club, mid-season. Participants: Twenty male professional football players over the age of 18, currently match fit with no injuries. Outcome measure: Proprioception was assessed by participants undertaking the moving target program on the balance module attached to a Kin-Com 125AP isokinetic dynamometer. A paired sample two tailed t -test was used to assess whether there was a significant difference between the participants test scores in the not taped and taped conditions. Results: The bilateral application of KT to professional footballers' ankles did not bring about a significant change in participants' scores when tested with a fine movement and balance control test. Percentage accuracy score mean difference 4.2 (p = 0.285). Conclusion: The results of this study do not support the use of KT when applied to the ankles of healthy footballers as a method of improving proprioception. Highlights: Randomised crossover study investigating the effects of kinesiology tape. Proprioception was assessed in professional soccer players with and without tape. A standing fine movement and balance control test evaluated proprioception. There was no improvement in players' test scores when wearing kinesiology tape.